Por ser de lá: a tutela jurídica da mulher nordestina sujeita a discriminação múltipla com base em gênero, origem e cultura - Rosa, Mariana Camilo Medeiros (2018)
This work was developed from the multidisciplinary analysis of the process experienced by women of Northeast Region of Brazil in the construction of their identities of gender, regional origin and cultural identity, and the creation, by legal science, of rights to equality and antidiscrimination protection capable of protecting them. The objective was to analyze the international and national normative set, applicable on the protection of the northeastern women and the mechanisms of guarantee of effectiveness to these norms in Brazil. By using methods of deductive and exploratory approach, through bibliographic research, it was possible to reach some conclusions. Firstly, that humanistic protection against discrimination by origin refers to the ancestry of the person, so that it is possible to protect it when the basis of the discriminatory act is its regional origin, so that this protection covers situations in which the victim of discrimination is a northeastern person. It was seen that, although there is no express provision in Brazilian legislation aimed at combating discrimination based on regional origin, there is a possibility of protection in Brazilian Law in owing to the incorporation of related international standards. Also, it was understood that the application of the criminal type provided for in article 20, § 2º of Law 7716 / 1989 in case of discrimination based on regional origin, current practice of the Brazilian Judiciary, is not appropriate, because it faces the constitutional principle of legal reserve. In this sense, it was noted the importance of approving the Bill nº 238/2017, currently being processed by the Federal Senate, which creates a specific criminal type applicable to the case. In addition, it is concluded that the opening in article 3, IV, of the Federal Constitution provides for the legal prohibition of other forms of discrimination, including intersectional discrimination based on gender and regional origin or cultural identity practiced against multiple northeastern women. Finally, the need of using an interpretation under intersectional bias by Brazilian Law applicators was defended on the analysis of cases of multiple discrimination suffered by women of Nordeste, including in judicial decisions.